A NEW CLASS OF EQUILIBRIUM GEOTHERMS IN THE DEEP THERMAL LITHOSPHERE OF CONTINENTS - Lenardic A.; Moresi L. (My University, 2000)
Equilibrium lithospheric geotherms are generally assumed to have a self-similar shape with a nearly linear thermal gradient in the upper portions of the thermal lithosphere and a smoothly decreasing gradient in its lowermost portions. Large thermal gradient increases are thought to be unsustainable because they would seem to imply a local heat flux imbalance that would be smoothed away over time. Simulations of mantle convection, allowing for continents, lead us to suggest that this may not be the case and that kinked geotherms may exist in thermal equilibrium within specific continental regions. This new class of geotherms arises from the coexistence of two heat loss modes within the continental lithosphere. Oceanic heat loss is dominated by convection, i.e., plate creation and subduction. Continental heat transfer, on the other hand, is of a conjugate nature with conduction dominating in stable, chemically buoyant portions of continental lithosphere and convection operating in its weaker lower portions. At the ocean-continent boundary, horizontal heat transfer occurs within a zone of accommodation where oceanic and continental heat loss are reconciled. If continents are underlain by mantle downwellings then this horizontal heat transfer can involve a convective pattern that allows weak lower portions of the thermal lithosphere to flow differentially below a passive continental margin. Horizontal advection can thus be low in the near surface regions of the margin, leading to mild thermal gradients, but can outweigh vertical conduction at depth, leading to steep gradients. This allows inflected, i.e., kinked, geotherms to be generated. Downstream of the margin, the thermal structure of the lower lithosphere adjusts to that of the continental interior and inflections decay. However, within a finite downstream region, inflected geotherms can be maintained indefinitely by continued sub-continental flow. A similar situation can occur when weak lower portions of the continental thermal lithosphere flow from thinner to thicker regions of chemically stabilized upper lithosphere.
Keywords: HEAT FLOW; CONTINENTAL CRUST; LITHOSPHERE; MANTLE; CONVECTION